2019
DOI: 10.1002/adma.201808222
|View full text |Cite
|
Sign up to set email alerts
|

Diffused Lattice Vibration and Ultralow Thermal Conductivity in the Binary Ln–Nb–O Oxide System

Abstract: In the pursuit of low thermal conductivity materials for thermal management, one always tries to increase the material entropy by increasing the number of components in the materials to scatter heat‐carrying phonons. However, it also drastically increases the technological complexity to synthesize materials with the target complex composition. Here, a material family is presented with simple composition Ln3NbO7, which only contains binary oxides of Ln2O3 (Ln = Dy, Er, Y, Yb) and Nb2O5. The thermal conductiviti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 40 publications
5
63
0
Order By: Relevance
“…b) Temperature‐dependent κ of the Ln 3 NbO 7 oxides compared with typical TBC materials. Reproduced with permission . Copyright 2019, Wiley‐VCH.…”
Section: High‐temperature Thermal Transport In Dense Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…b) Temperature‐dependent κ of the Ln 3 NbO 7 oxides compared with typical TBC materials. Reproduced with permission . Copyright 2019, Wiley‐VCH.…”
Section: High‐temperature Thermal Transport In Dense Materialsmentioning
confidence: 99%
“…Different from aforementioned studies which focused on increasing the number of components to enhance phonon scattering and reduce κ, Yang et al developed another material family, Ln 3 NbO 7 , containing only binary oxide Ln 2 O 3 and Nb 2 O 5 . As shown in Figure b, the fours type of materials all showed low κ below 1.5 W m −1 K −1 at room temperature, and thermally outperforms a variety of TBC materials in the entire temperature range from room temperature to 1000 °C.…”
Section: High‐temperature Thermal Transport In Dense Materialsmentioning
confidence: 99%
“…It was found that, as shown in Figure , the crystal structures of RE 3 NbO 7 are fluorite structure (cubic) with space group Fm‐3m where RE and Nb atoms randomly occupy the positions of 4 a cations by the ratio of 3:1, and 1/8 of the oxygen sites on the 8 b position is vacant to keep the chemical balance. Especially, those compounds show pronounced disordering of cations and the random distribution of oxygen vacancies over anion sites, which was confirmed by both Raman spectrum and high‐resolution transmission electron microscope (HRTEM) analysis …”
Section: Methodsmentioning
confidence: 74%
“…In RE 3 NbO 7 compound, there are mainly two types of ionic bonding, RE 3+ –O 2‐ and Nb 5+ –O 2‐ . The large difference in length and strength of these two bonding leads to a large chemical inhomogeneity . This finally results in softening of the lattice and reduced elastic constant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation